OP0148 The Effect of Biological Agents on Work in Patients with Chronic Inflammatory Arthritides: A Meta-Analysis of Randomized Controlled Trials and Controlled Cohorts. (9th June 2015) - Tubery, A.; Castelli, C.; Erny, F.; Barchechath-Flaisler, F.; Dadoun, S.; Fautrel, B.; Gaujoux Viala, C.
Abstract : Background: The addition of biological agents in chronic inflammatory arthritides (CIAs) therapeutic strategies has improved the possibility of controlling disease activity and slowing the progression of joint damage. However their impact on work participation remains unclear. Objectives: To assess the effect of biological agents on work among patients with chronic inflammatory arthritides. Methods: A systematic review of the literature using Pubmed-Medline and the Cochrane library was performed until January 2014. All randomized controlled trials (RCTs) and controlled cohorts (CCs) reporting the effect of biological agents on work among patients with rheumatoid arthritis (RA), ankylosing spondylitis (AS) or psoriatic arthritis (PsA) were selected. Data extraction: Data were collected using a predetermined form. The outcomes were accumulated missed workdays, number of patients losing worktime due to CIAs, impact on productivity (on a visual analogue scale) and employment loss. Statistical analysis determined in each study effect size (ES) or odds-ratios (OR) as appropriate to assess the magnitude of treatment effect. Pooled ES and OR were computed by meta-analysis. A random effect model was used in case of heterogeneity. Results: 15 RCTs and 7 CCs were analyzed i.e. 15881 patients treated by biological agents (adalimumab, etanercept, infliximab, certolizumab, golimumab and abatacept) and 9713 controls. Among those 25594 patients, 24670 suffered from RA, 319 from AS, and 605 from PsA. Pooled analyses indicated that biological agents significantly reduced accumulated missed workdays at week 24 (2 trials): SRM= -0.34 [95%CI -0.60 to -0.08], the number of patients losing hours (3 trials): OR=0.54 [95%CI 0.36 to 0.79] and improved work productivity (3 trials): ES=-1.58 [95%CI -2.66 to -0.51]. The positive effect on employment loss was nearly significant (8 trials): OR=0.60 [95% CI 0.33 to 1.09]. Conclusions: Despite the heterogeneity of the data, this meta-analysis showed the beneficial effect of biologics agents on both absenteeism and presenteeism in chronic inflammatory rheumatism. Thus the high cost of biologic agents could be partly balanced with savings in indirect costs. Disclosure of Interest: A. Tubery: None declared, C. Castelli: None declared, F. Erny Speakers bureau: Abbvie; Amgen, F. Barchechath-Flaisler Speakers bureau: Abbvie; Amgen, S. Dadoun: None declared, B. Fautrel Speakers bureau: Abbvie, BMS, MSD, Nordic-Pharma, Pfizer, Roche-Chugai, UCB, C. Gaujoux Viala Consultant for: Abbvie, BMS, Janssen Pharmaceutica Product LP, MSD, Nordic-Pharma, Pfizer Inc, UCB, Roche Pharmaceuticals